2014
DOI: 10.1162/jocn_a_00641
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Learning of Simple Stimuli Modifies Stimulus Representations in Posterior Inferior Temporal Cortex

Abstract: Practicing simple visual detection and discrimination tasks improves performance, a signature of adult brain plasticity. The neural mechanisms that underlie these changes in performance are still unclear. Previously, we reported that practice in discriminating the orientation of noisy gratings (coarse orientation discrimination) increased the ability of single neurons in the early visual area V4 to discriminate the trained stimuli. Here, we ask whether practice in this task also changes the stimulus tuning pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 56 publications
(59 reference statements)
7
45
0
Order By: Relevance
“…Switching attention between trained and untrained locations did not trigger the training-induced shift in PNE, indicating that learning-induced changes arose from long-lasting enhancements in neurons’ ability to represent stimulus contrast differences, rather than to attention-evoked or other task-evoked modulations of firing rates (see also Supplementary note 10 ). This is in line with data from posterior inferior temporal area, which is hierarchically close to area V4 12 . Interestingly, the results are different from similar studies in area V1 41 , where neural correlates of perceptual learning were task-dependent, and thus possibly related to selective attention 7 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Switching attention between trained and untrained locations did not trigger the training-induced shift in PNE, indicating that learning-induced changes arose from long-lasting enhancements in neurons’ ability to represent stimulus contrast differences, rather than to attention-evoked or other task-evoked modulations of firing rates (see also Supplementary note 10 ). This is in line with data from posterior inferior temporal area, which is hierarchically close to area V4 12 . Interestingly, the results are different from similar studies in area V1 41 , where neural correlates of perceptual learning were task-dependent, and thus possibly related to selective attention 7 .…”
Section: Discussionsupporting
confidence: 90%
“…refs. 9 12 ). Only one study has analysed striate cortex (V1) activity from multiple chronically implanted electrodes during learning.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gilbert and colleagues found that while perceptual training on an embedded contour detection task has little effect on basic response properties of monkey V1 neurons, it has a pronounced effect on how V1 neurons are modulated by stimulus context (6,56,71). This finding stands in contrast to those described above from V4 (57,70) and primary ACx (9)(10)(11)(12), where it was found that training modified stimulus-encoding properties. These apparent dissimilarities may reflect differences among functional networks, behavioral tasks, or species.…”
Section: Significancementioning
confidence: 86%
“…These studies report that trained animals display altered auditory cortical responses, such as tonotopic reorganization (9,12) and enhanced AM processing (10,11). Similarly, Adab and colleagues recorded from V4 and posterior inferior temporal cortex neurons of awake monkeys during training on an orientation discrimination task (57,70). The authors found that training enhanced the responses to the orientation gratings, and the enhancements were present both during task performance and during passive fixation.…”
Section: Significancementioning
confidence: 95%
“…It is unlikely that this reflects visual experience alone. Moreover, some studies have shown that fMRI activity patterns are immune to visual training and familiarization in adult monkeys [27,28], although the activity magnitudes may change [29]. Taken together, representational changes in the PIT would be, at least in part, crossmodal effects caused by simultaneous exposure to the visual and haptic features of objects.…”
Section: Representation Of Non-visual Information In the Ventral Visumentioning
confidence: 99%